Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Perdagangan Orang - Nugroho, Adi Purwo; Titahelu, Juanrico Alfaromona Sumarezs; Latupeirissa, Julianus Edwin (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
The purpose of this writing is to analyze and explain the factors of child trafficking in Aru Regency. The crime of trafficking in persons is generally in the form of violations of human dignity and dignity in the form of cruel treatment, and even slavery-like treatment. This perpetrator is accepted as the helplessness of the victim, who is trapped in a network that is very difficult to identify, so it will be difficult to find a solution. The research method used in this research is normative legal research, namely legal research conducted by analyzing literature materials.